Glycemic Control and the Outcomes of Hispanic Patients with Diabetes Admitted to the General Ward of a Community Hospital in Puerto Rico - Torres-Torres, Nancy (P R Health Sci J, 2011)
OBJECTIVE: Uncontrolled glucose, present in 40% of diabetic patients admitted to United States hospitals, has been associated with prolonged length of stay and poorer general outcomes in critically ill and surgical patients. However, past studies of general ward patients have shown there to be no consistent benefits of strict glucose control, and the Hispanic population has been underrepresented in such studies. This work evaluated the association between glycemic control and the outcomes of hospitalized Hispanics with diabetes and to describe physicians’ interventions in the treatment of diabetes. METHODS: This is a retrospective chart review of all patients with diabetes admitted over a period of six months in the general ward of a community hospital in Puerto Rico. We evaluated glucose levels during the first 72 hours, length of stay, and reported complications during admission. Outcomes were evaluated with crude odds ratios and multivariate logistic regression. RESULTS: Uncontrolled blood glucose was observed in 59.1% of the 875 patients whose records were revised; of that 59.1%, treatment modification was not prescribed for 43.2%. Patients with poorly controlled glucose were more likely to develop acute coronary syndrome (corrected OR: 11.46; 95% CI = 1.48 – 88.50) as a complication and less likely to develop hypoglycemia (corrected OR: 0.57; 95% = CI 0.37 – 0.88). CONCLUSION: Our results suggest that hospitalized but non-critically ill Hispanic patients with diabetes are prone to poor outcomes secondary to uncontrolled glucose levels; in addition, those results support the creation of standardized protocols for the management of diabetes in this population.